Open innovation and determinants of technology-driven sustainable value creation in incubated start-ups - Iveta Cirule; Inga Uvarova (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Business incubators ensure networking and facilitate Open Innovation (OI) collaborations both inside the incubator among entrepreneurs and outside with external stakeholders. Recently, the sustainability and the promotion of environment-friendly businesses has become an important focus for the business incubators. Sustainability-oriented business incubation is a relatively new and emerging topic both for scholars and BI practitioners. This paper aims to explore the theoretical groundings for the business incubation perspectives in facilitating sustainable value creation through OI approaches and to test research instruments exploring determinants of the technology-driven sustainable value creation in incubated start-ups in Latvia. Through the pilot survey, this study will also increase the awareness on the importance of the OI and the creation of sustainable value, and provides the preliminary results to be considered by scholars and practitioners. Results show that climate change, as a planetary boundary, positively stimulates incubated start-ups to improve their technology-driven sustainable value creation. However, sustainability ambition, if negatively influenced by the incubator location, negatively affects the technology-driven sustainable value creation. These results on the sustainability scale within the business incubation of start-ups contribute to the new theoretical concepts, related to integration of the sustainability issues and OI practices within business incubation.
Keywords: 650; incubated start-ups; Latvia; planetary boundaries; sustainable ambition; sustainable strategy; technology-driven sustainable value creation